Optimization of cadastral adjustment using angular data observation / Muhammad Firdaus Md Zaidi - Md Zaidi, Muhammad Firdaus (2022)
Accuracy in cadastral database very important to help the national development. In Malaysia, the bearing was used as the main data for cadastral adjustment and is generated by a mathematical computation depending on the angle of the survey equipment. However, the mathematical calculation for producing the bearing have been an issue on systematic error due to indirect measurement. This will lead to data acquisition errors spreading, resulting in low positional accuracy in cadastral databases. To reduce systematic error in the calculation, angle measurement is an option for direct measurement in data acquisition implement to cadastral survey and cadastral adjustment. Therefore, the purpose of this study is to assess optimization of cadastral adjustment using angular data observation. The method that been use for this study are comparison between bearing and angular method. Both of method results will be analysed based on statistical analysis such residual, range, mean and standard deviations. The result of this paper will show that the angular method will be the best option to reduce the error in cadastral work.